2011
DOI: 10.1371/journal.pone.0020034
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Increases Epidermal Growth Factor Receptor Signaling and Promotes Tumor Progression in Advanced Human Prostate Cancer

Abstract: Genistein is an isoflavone found in soy, and its chemo-preventive and -therapeutic effects have been well established from in vitro studies. Recently, however, its therapeutic actions in vivo have been questioned due to contradictory reports from animal studies, which rely on rodent models or implantation of cell lines into animals. To clarify in vivo effects of genistein in advanced prostate cancer patients, we developed a patient-derived prostate cancer xenograft model, in which a clinical prostatectomy samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 52 publications
4
45
0
Order By: Relevance
“…Although the initial impetus for these studies related to the treatment of accidentally exposed individuals, genistein is also of interest therapeutically for cancer patients. It has been reported to inhibit invasion, metastasis and angiogenesis in vitro and in vivo in a number of cancers, including breast cancer, although recent data have questioned its effect in prostate cancers (4957). A recent pilot study has reported that treatment with an isoflavone cocktail including genistein can reduce side effects after radiation treatment of prostate cancer (58).…”
Section: Discussionmentioning
confidence: 99%
“…Although the initial impetus for these studies related to the treatment of accidentally exposed individuals, genistein is also of interest therapeutically for cancer patients. It has been reported to inhibit invasion, metastasis and angiogenesis in vitro and in vivo in a number of cancers, including breast cancer, although recent data have questioned its effect in prostate cancers (4957). A recent pilot study has reported that treatment with an isoflavone cocktail including genistein can reduce side effects after radiation treatment of prostate cancer (58).…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of literature with respect to the effects of isoflavones on EGFR signaling. Importantly, the most prevalent isoflavone in soy is genistein, which can reduce EGF-mediated DNA synthesis (163), decrease EGFR levels (164, 165), decrease or increase phosphorylation of EGFR (166, 167), and transactivate EGFR (168). …”
Section: Transgenic Egf Sif To Treat Necrotizing Enterocolitismentioning
confidence: 99%
“…A number of concerns have been raised about the estrogen-like effects of natural isoflavones (i.e., the possible promotion of estrogen-sensitive cancers) [542–544]. However, a recent nested case-control study and meta-analysis of numerous epidemiological studies show an inverse correlation between GEN intake and breast cancer risk and a number of other clinical studies support the breast and uterine safety of purified naturally derived GEN administered for up to 3 years [545].…”
Section: Low Toxicity Approachesmentioning
confidence: 99%